Unusual case of adult-onset cutaneous lupus erythematosus mimicking early mycosis fungoides - Hanof Ahmed (16494866) (2023)
Discoid lupus erythematosus (DLE) is a chronic variant of cutaneous lupus erythematous developing on sun-exposed areas in multi-morphic forms making diagnosis challenging. Clinical suspicion and prompt treatment are necessary to avoid permanent disfigurement, progression to systemic involvement and poor quality of life. We report a case of delayed DLE diagnosis in a 45-yearold man who presented with a new skin lesion mimicking the early stages of mycosis fungoides that prompted further investigation. Histopathological examination confirmed DLE and appropriate treatment was initiated. However, the atypical clinical presentation led to disseminated DLE and refractory disease control, resulting in scarring and cosmetic disfigurement. Other Information Published in: Oxford Medical Case Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1093/omcr/omad043